Glycan analysis of Fonsecaea monophora from clinical and environmental origins reveals different structural profile and human antigenic response - Burjack, Juliana R.; Santana-Filho, Arquimedes P.; Ruthes, Andrea C.; Riter, Daniel S.; Vicente, Vania A.; Alvarenga, Larissa M.; Sassaki, Guilherme L. (Frontiers in Cellular and Infection Microbiology, 2014)
Dematiaceous fungi constitute a large and heterogeneous group, characterized by having a dark pigment, the dihydroxynaftalen melanin—DHN, inside their cell walls. In nature they are found mainly as soil microbiota or decomposing organic matter, and are spread in tropical and subtropical regions. The fungus Fonsecaea monophora causes chromoblastomycosis in humans, and possesses essential mechanisms that may enhance pathogenicity, proliferation and dissemination inside the host. Glycoconjugates confer important properties to these pathogenic microorganisms. In this work, structural characterization of glycan structures present in two different strains of F. monophora MMHC82 and FE5p4, from clinical and environmental origins, respectively, was performed. Each one were grown on Minimal Medium (MM) and Czapeck-Dox (CD) medium, and the water soluble cell wall glycoconjugates and exopolysaccharides (EPS) were evaluated by NMR, methylation and principal component analysis (PCA). By combining the methylation and 2D NMR analyses, it was possible to visualize the glycosidic profiles of the complex carbohydrate mixtures. Significant differences were observed in β-D-Galf-(1→5) and (1→6) linkages, α- and β-D-Glcp-(1→3), (1→4), and (1→6) units, as well as in α-D-Manp. PCA from 1H-NMR data showed that MMHC82 from CD medium showed a higher variation in the cell wall carbohydrates, mainly related to O-2 substituted β-D-Galf (δ 106.0/5.23 and δ 105.3/5.23) units. In order to investigate the antigenic response of the glycoconjugates, these were screened against serum from chromoblastomycosis patients. The antigen which contained the cell wall of MMHC82 grown in MM had β-D-Manp units that promoted higher antigenic response. The distribution of these fungal species in nature and the knowledge of how cell wall polysaccharides and glycoconjugates structure vary, may contribute to the better understanding and the elucidation of the pathology caused by this fungus.